Clinical efficacy of joint mobilization for shoulder impingement syndrome: a systematic review and meta-analysis - Gayeong Lee; Hyeonjun Woo; Yunhee Han; Seungkwan Choi; Jungho Jo; Junghan Lee; Seojae Jeon; Wonbae Ha (PLoS ONE, 2026)
Background No systematic review has examined the clinical effectiveness of mobilization for shoulder impingement syndrome (SIS). We aimed to evaluate clinical effectiveness for the use of mobilization in SIS. Methods PubMed, Embase and the Cochrane Library were searched for studies published up to April 30, 2023. Randomized controlled trials that evaluated the effectiveness of mobilization for SIS were included. Literature was extracted using Endnote 20, and the risk of bias was assessed using the Cochrane risk-of-bias tool 2.0. A meta-analysis was conducted using RevMan 5.4. This study was conducted in accordance with the PRISMA guidelines. Results Nineteen randomized controlled trials (956 participants) were selected based on the inclusion criteria. Adding mobilization to traditional physical therapy reduced pain (mean difference [MD]=1.72, 95% confidence interval [CI]: 0.91 to 2.53, I 2 = 97%, p < 0.00001), increased active range of motion (MD = 14.49, 95% CI: 8.46 to 20.53, I 2 = 95%, p < 0.00001), and improved the disabilities of the arm, shoulder, and hand (MD = 5.95, 95% CI: 0.01 to 11.90, p = 0.05) and Constant-Murley scores (MD = 5.49, 95% CI: 0.78 to 10.19, p = 0.02). Joint mobilization was more effective in reducing pain (MD = 0.67, 95% CI: 0.15 to 1.19, p = 0.01) and increasing active range of motion (MD = 8.56, 95% CI: 2.31 to 14.82, p = 0.007) compared with sham mobilization. No statistically significant differences were found between physical therapy plus mobilization and physical therapy plus exercise. Conclusion Mobilization may offer adjunctive, short-term benefits in improving the clinical symptoms of SIS when added to conventional treatments. Future studies should focus on evaluating the effects of mobilization as a stand-alone intervention, incorporate larger sample sizes and long-term follow-up, and conduct high-quality comparative trials to identify the most effective specific mobilization techniques.